Computer-modified paramedian approach technique reduces failures and alleviates pain in lumbar puncture: a prospective comparative study - Zhuang, Yuan-Dong; Xie, Hai-Shu; Chen, Jing; Wu, Guo-Hua; Wu, Jian-Feng; Chen, Chun-Mei (Frontiers in Medicine, 2024)
Background: The conventional midline approach for lumbar puncture (MAT-LP) has a relatively low success rate of 70%. The paramedian approach can increase the effective puncture area and success rate but lacks standardized guidelines. This study evaluated a computer-modified paramedian approach technique (CMPAT) to optimize lumbar puncture using computational techniques. Methods: In this prospective study, 120 patients underwent CMPAT-LP (n=60) or MAT-LP (n=60). Puncture failure was defined after 6 attempts. Failure rate, number of attempts, pain score, and complications were compared. Subgroup analysis was conducted for age (≥ 50 years). Results: No significant demographic differences existed between groups. Failure rates were 3.3% for CMPAT vs. 13.3% for MAT. Puncture attempts averaged 2.02 vs. 3.53, and pain scores were 2.68 vs. 4.13 for CMPAT and MAT, respectively. All outcomes were significantly improved with CMPAT, especially in elderly patients. No significant difference in complications was observed. Conclusions: Compared to MAT, CMPAT-LP demonstrated lower failure rates, fewer puncture attempts, and less pain, without compromising safety. CMPAT may be superior and should be more widely implemented in clinical practice.